Multi-scale modelling of polymer composite materials at high rates of strain - Lidgett, Mark Jonathan (2012)
The overall objective of this thesis was to develop a methodology for predicting the high strain rate properties of macro scale polymer composite materials through micro and meso scale finite element modelling. The focus in this study was on multi-layered multi-material polymer composite laminates consisting of 0/90 and ± 45 layers of either; S2 Glass/Epoxy or Carbon/Epoxy non crimp fabric. A multi-scale finite element modelling methodology was developed at the micro and meso scale for predicting the elastic response, damage initiation, damage evolution and strain rate dependence of macro scale polymer composite materials. The methodology was implemented in the Abaqus finite element package utilising Python scripting for simulation definition and Fortran code for user defined explicit material subroutines. Micro scale unit cells were tested in longitudinal, transverse and shear loading directions over a range of strain rates. The results of the micro scale testing were converted into material properties of the meso scale yarns / tows. Meso scale unit cells were tested in in-plane, through thickness and shear loading directions over of a range of strain rates. The results of the meso scale testing were converted into material properties of macro scale polymer composite materials. The modelling methodology was validated against experimental testing conducted on meso scale samples over a range of strain rates using an electromechanical universal static test machine and an instrumented falling weight drop tower. The contribution to knowledge from this study is the development of a validated modelling methodology for predicting the elastic, damage and strain rate dependent response of polymer composite materials at a micro and meso scale.